The Influence of Corporate Social Responsibility, Good Corporate Governance, and Intellectual Capital on Company Value and Financial Performance: Pengaruh Corporate Social Responsibility, Good Corporate Governance, dan Intellectual Capital terhadap Nilai Perusahaan dan Kinerja Keuangan - Vivi Dwi Anggreini; Wiwit Hariyanto (Academia Open, 2021)
In the current era of globalization, companies are growing rapidly, besides the current economy is less stable. In this case Corporate Social Responsibility, Good Corporate Governance and Intellectual Capital are very important to be implemented. With the aim of knowing whether Corporate Social Responsibility, Good Corporate Governance, and Intellectual Capital have an effect on Company Value and Financial Performance in Food and Beverages Companies listed on the Indonesia Stock Exchange for the 2015-2019 Period. This research method uses quantitative research. The type of data in this study is secondary data with data collection techniques using the documentation method. The sample used is Food and Beverages companies listed on the Indonesia Stock Exchange for the 2015-2019 period using the purposive sampling method. The data analysis technique used is descriptive statistical analysis, classical assumption test, and multiple linear regression analysis. The results of this study indicate that Corporate Social Responsibility has no effect on firm value, good corporate governance has no effect on firm value, intellectual capital has no effect on firm value, corporate social responsibility has no effect on financial performance, good corporate governance has no effect on financial performance, and intellectual capital effect on Financial Performance.